Practical reality experienced by nurses in risk classification in emergency and emergency services (Research, Society and Development, 2022)
Objective: To identify in the literature the reality experienced by nurses in the context of risk classification in urgent and emergency services. Methodology: Theoretical study of the integrative literature review (RIL) type, with the purpose of gathering and synthesizing the results of studies already carried out. The research was carried out by pairs, between the months of July and September 2021, in the Virtual Health Library (VHL), using the descriptors: Urgency and Emergency Services and Risk Classification. The research population included 210 documents; later, a critical and reflective reading of the titles and abstracts was carried out, and correlation with the guiding question; thus, a sample of 14 articles was established. Results: Nurses are professionals who acquire, in their training, the skills and abilities necessary for risk screening and classification, as they have a clinical language oriented to the signs and symptoms presented by the user, and not to the diagnoses, necessarily, achieving establishing an empathetic relationship, which is essential in minimizing feelings such as anxiety, aggression or impatience, and calmly explaining to the user the purpose of the screening process. Conclusion: The nurse is seen as a key figure in this process, so that the need for training and training is reiterated, in order to standardize as much as possible the risk classification assigned by them. It was also evidenced that to guarantee and continuity of care, it is imperative to apply the Systematization of Nursing Care.